Calcium Doping Facilitates Water Dissociation in Magnesium Oxide. (11th December 2017) - Müller, Danny; Knoll, Christian; Ruh, Thomas; Artner, Werner; Welch, Jan M.; Peterlik, Herwig; Eitenberger, Elisabeth; Friedbacher, Gernot; Harasek, Michael; Blaha, Peter; Hradil, Klaudia; Werner, Andreas; et al.
Abstract: Calcium doping of magnesium oxide results in significantly increased water dissociation rates, thus enhancing both hydration rate and reaction completeness of hydration compared to pure MgO. For a series of mixed magnesium–calcium oxides (Mg x Ca1− x O) with varying Ca contents between 0% and 40%, the material of a composition Mg0.9 Ca0.1 O shows the fastest rehydration, transforming completely within 80 min to the mixed hydroxide. In consecutive dehydration/rehydration cycles, reasonable cycle stability is found. A "regeneration" of the aged material (reactivity reduced by excessive cycling) in liquid water re‐establishes the initial rehydration reactivity. Density functional theory calculations support the experimental findings, confirming that calcium doping can reduce the energy of the rate limiting water dissociation reaction, exploiting both electronic and steric (size) effects. Abstract : The water dissociation ability of Ca‐doped MgO is significantly enhanced compared to pure MgO, based on a decrease in the kinetic barrier of the water dissociation step due to electronic and steric (size) effects. This allows for a complete conversion of an Mg0.9 Ca0.1 O phase within 80 min to the corresponding mixed hydroxide.